David Lean's Brief encounter - Mathieson, Muir 1911-1975; Coward, Noël 1899-1973 (Criterion Coll., 2000)
Trevor Howard and Celia Johnson star as middle-class suburbanites whose casual friendship evolves into a passionate yearning for each other. But as their affections grow stronger, they must face a difficult decision that will affect both of their lives forever.
The digital transfer, with restored image and sound, was created from a 35 mm composite fine-grain master, made from the original camera negative
Bildformat: 1.33:1 aspect ratio
Orig.: Großbritannien 1946
Enth. audio commentary by film historian Bruce Eder ; restoration demonstration ; original theatrical trailer
Keywords: Homemakers - Drama; Marriage - Drama; Railroad stations - Drama; Housewives -- Drama; Marriage -- Drama; Railroad stations -- Drama; Feature films